2013
DOI: 10.1021/es402664t
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater Dissolved Organic Matter: Influence of Land Cover and Environmental Factors

Abstract: Dissolved organic matter (DOM) plays a major role in defining biological systems and it influences the fate and transport of many pollutants. Despite the importance of DOM, understanding of how environmental and anthropogenic factors influence its composition and characteristics is limited. This study focuses on DOM exported as stormwater from suburban and urban sources. Runoff was collected before entering surface waters and DOM was characterized using specific ultraviolet absorbance at 280 nm (a proxy for ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 76 publications
9
54
0
Order By: Relevance
“…The size properties of DOM have also been connected to its source (McElmurry et al, 2013), its effectiveness as a binding agent for metals (Benedetti et al, 2002;Wu et al, 2004;Chen et al, 2013), and its DBP formation potential (Hur et al, 2012). Thus, both the fluorescence and size properties of DOM are related to its functionality; however, little is known about relationships between its size and fluorescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…The size properties of DOM have also been connected to its source (McElmurry et al, 2013), its effectiveness as a binding agent for metals (Benedetti et al, 2002;Wu et al, 2004;Chen et al, 2013), and its DBP formation potential (Hur et al, 2012). Thus, both the fluorescence and size properties of DOM are related to its functionality; however, little is known about relationships between its size and fluorescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…DON concentrations are affected by climate variables, biological processes and hydrography conditions (Williams et al 2001;Yano et al 2005;McElmurry et al 2014). Released DON from submerged macrophytes and benthic algae is likely to be another significant N input to shallow lakes (Berman and Bronk 2003).…”
Section: Introductionmentioning
confidence: 99%
“…). An ephemeral stream draining a golf course in Michigan reported annual average dissolved organic matter (DOM) at 21.6 mg L -1 [22]. Other studies of DOC in urban surface waters have reported lower DOC concentrations; for example a study of an urban and forested stream in Florida reported mean annual urban surface water DOC concentrations of 13 mg L -1 compared to forest surface water concentrations of 26 mg L -1 [23].…”
Section: Discussionmentioning
confidence: 99%